'Clean hands' in derivative actions - Payne, J (Cambridge University Press, 2002)
This article challenges the commonly expressed view that shareholders wishing to bring a derivative action on behalf of the company must have 'clean hands' i.e. that there must be nothing in the shareholders behaviour which renders it unjust to allow the derivative action to proceed. While minority shareholders' misbehaviour might well have consequences for themselves, such as requiring the repayment of dividends known to have been paid unlawfully, those actions ought, in the normal course of events, to be irrelevant for the purpose of deciding whether to allow a derivative action to proceed. This article suggests some circumstances in which a minority shareholder's situation or actions may affect the decision to allow a derivative action brought by that particular shareholder to proceed, but these do not spring from the clean hands doctrine, but rather from the particular factual circumstances of the case or from an entirely proper desire on the court's part to use the derivative action only where it is necessary to achieve justice for the company.